2020
DOI: 10.1159/000507922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Physical Movement Activity and Multifaceted Cognitive Training in Older People with Mild Neurocognitive Disorder in a Rural Community: A Randomized Control Trial

Abstract: Introduction: Cognitive deterioration in older people with mild neurocognitive disorders (mNCD) increases the risk of progress to major NCD. Health professionals worldwide are trying to find strategies for prevention. There is a limited number of studies that deal with cultural conditions in northern Thailand. Objectives: This study aimed to investigate the effects of a combination of physical movement activity and multifaceted cognitive training on cognitive function in older people with mNCD. Methods: A rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Participants’ mean ages were obtained from baseline characteristics for most of the studies except for Griffiths et al (2020) , which only included the number of participants in two age groups (60–69 years) and (70–79 years). Mean ages ranged from 67.82 to 87.20 with a standard deviation of 4.26.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants’ mean ages were obtained from baseline characteristics for most of the studies except for Griffiths et al (2020) , which only included the number of participants in two age groups (60–69 years) and (70–79 years). Mean ages ranged from 67.82 to 87.20 with a standard deviation of 4.26.…”
Section: Resultsmentioning
confidence: 99%
“…Verbal fluency measured through semantic and category fluency tests was the domain with the lowest pooled effect size compared to other domains ( g = 0.45, 95% CI = [0.18, 0.73]) ( Figure 6F ). Among the studies that assessed changes in verbal fluency and confrontational naming, two ( Shimada et al, 2018 ; Griffiths et al, 2020 ) reported significant improvements while one noted comparable changes in both groups ( Rojas et al, 2013 ; control: mean change = 2.40, p < 0.01; intervention: mean change = 2.40, p < 0.01). Similar to executive function, lower verbal fluency scores in older adults with MCI could predict progression to AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the beneficial effects on divers cognitive domains, they also indicated that physical activity/exercise significantly decreased risk and number of falls, and that physical activity/exercise may improve depression and behavioral and psychological symptoms in dementia [28]. Finally, some recent randomized controlled trials have shown that a combined exercise and cognitive training improves attention, concentration, cognitive function and activities of daily living in dementia patients [31] and is effective in delaying/preventing cognitive deterioration and cognitive functional decline in people with MCI [32]. Although there is no consensus on the most effective modalities, it is remarkable that exercise (single- or multicomponent) seems to be a constant key factor in this context.…”
Section: Discussionmentioning
confidence: 99%
“…With an adherence rate of 82.6%, authors found a significant increase in cognition in the Baduanjin compared to non-exercise group (p = .050). Griffiths et al (2020) tested a physical movement (up to 30 minutes) and cognitive stimulating (up to 90 minutes) activities intervention over 12 weeks, without using of technology and led by three occupational therapists. The intervention found improvements in attention (p = 0.018), memory (immediate, p = 0.001; delayed recall, p = 0.001).…”
Section: Studies Rated As Highest Quality (N=2)mentioning
confidence: 99%